Sequential electrospinning of multilayer ethylcellulose/gelatin/ethylcellulose nanofibrous film for sustained release of curcumin. (5th March 2020) - Wang, Peng; Li, Yang; Zhang, Cen; Feng, Fengqin; Zhang, Hui
Highlights: The ethylcellulose/gelatin/ethylcellulose film was fabricated by sequential electrospinning. The multilayer film showed high thermal stability due to hydrogen bonds between two adjacent layers. The multilayer film exhibited a sustained release manner of the encapsulated curcumin for 96 h. The antioxidant activities of curcumin from the multilayer film were retained during the release. Abstract: In this work, sequential electrospinning was utilized to fabricate a multilayer film with ethylcellulose nanofibers as the outer layer and curcumin-loaded gelatin nanofibers as the inner layer. Field-emission scanning electronic microscopy observations showed that the outer and inner layers had a smooth surface and clear boundary. The hydrophobic outer layers decreased the water vapor permeability and improved the water contact resistance of the hydrophilic inner layer, and the intimate interactions of hydrogen bonds between two adjacent layers enhanced the thermal stability. The multilayer film exhibited a sustained release manner of the encapsulated curcumin for 96 h, compared to the burst release within 30 min from the gelatin film. In addition, the antioxidant activities of the released curcumin from the multilayer film were well retained within 96 h. These results suggested that the multilayer nanofibrous film fabricated by sequential electrospinning has potential applications in bioactive encapsulation and controlled release.